Acute Effect of Static Stretching Duration for Paravertebral Muscles on Lumbar Multifidus Myoelectric Activity: A Crossover Clinical Trial - Coracini, Camila Amaral (2024)
Introduction. Considering that stretching can reduce neural impulses, this study aimed to verify whether stretching to paravertebral muscles changes the electromyographic activity characteristics of the lumbar multifidus. Methods. The volunteers (n = 46) were randomly allocated to four experimental conditions performed in 4 visits: control and three paravertebral stretching interventions sustained for 10, 30, and 60 s. At each visit, the electromyographic activity of the multifidus was collected in the following sequence: a) pre-intervention in the neutral orthostatic position; b) during the intervention targeted by the visit; c) post intervention in the neutral orthostatic position. Outcomes were analyzed by MatLab codes using wavelet methodology. In addition to the inferential statistics generated by the generalized estimation equation model, it presented reproducibility and responsiveness metrics. Results. Only the median frequency difference between the sustained stretches for 10 and 60 s was found. However, responsiveness measures indicated that such a difference was due to measurement variability rather than the actual change caused by the intervention. Conclusions. Stretching duration did not influence the electrical activity of the lumbar multifidus. Study registration. This study was registered at Brazilian Registry of Clinical Trials-REBEC (number: RBR-7bvg7p): http://www.ensaiosclinicos.gov.br/.